Impact of foliar application of zinc and zinc oxide nanoparticles on growth, yield, nutrient uptake and quality of tomato - Ahmed, Razu; Uddin, Md. Kamal; Quddus, Md. Abdul; Abd Samad, Mohd Yusoff; Hossain, M. A. Motalib; Haque, Ahmad Numery Ashfaqul (MDPI, 2023)
Appropriate foliar application of zinc (Zn) and zinc oxide nanoparticles (ZnO-NPs) is important for the proper growth and yield of tomato. However, the effects of foliar application of Zn and ZnO-NPs were not well-studied on tomato production. A pot experiment was conducted at glasshouse (8D) conditions under the Faculty of Agriculture, Universiti Putra Malaysia (UPM) to evaluate the effectiveness of Zn and ZnO-NPs on growth, yield, nutrient uptake, and fruit quality of tomatoes and to compare between the Zn nutrient and ZnO-NPs. Treatment combinations were 14 viz. T1 = 0 (control), T2 = 1500 ppm (mg/L) Zn nutrient, T3 = 2000 ppm (mg/L) Zn nutrient, T4 = 2500 ppm (mg/L) Zn nutrient, T5 = 75 ppm ZnO nanoparticle, T6 = 100 ppm ZnO nanoparticle, and T7 = 125 ppm ZnO nanoparticle along with two tomato varieties. The experimental design was a split plot with four replications. Results indicated that foliar application of 100 ppm ZnO-NPs performed best in terms of growth parameters, physiological traits, yield attributes, yield, and quality traits of tomatoes. The same treatment (100 ppm ZnO-NPs) contributed to attain the highest nutrient uptake. Recovery use efficiency of Zn was highest with foliar application of 75 ppm ZnO-NPs. The highest yield increment (200%) over control was from foliar sprayed with 100 ppm ZnO-NPs. Comparing the two varieties, MARDI Tomato-3 (MT3) showed better than MARDI Tomato-1 (MT1). As is appears from the results, foliar application of zinc oxide nanoparticles was more efficient than conventional zinc fertilizer. Therefore, the foliar sprayed with 100 ppm ZnO-NPs can be suggested to improve quantity and quality of tomato in glasshouse soil conditions.